Charge/discharge and cycling performance of flexible carbon paper electrodes in a regenerative hydrogen/vanadium fuel cell. (15th November 2019) - Chakrabarti, Barun; Yufit, Vladimir; Kavei, Ashkan; Xia, Yuhua; Stevenson, Graham; Kalamaras, Evangelos; Luo, Hui; Feng, Jingyu; Tariq, Farid; Taiwo, Oluwadamilola; Titirici, Maria-Magdalena; Brandon, Nigel
Abstract: The regenerative hydrogen/vanadium fuel cell (RHVFC) is investigated with Freudenberg carbon paper electrodes (CPs). Along with thermal treatment, the Freudenberg CPs are also treated with reduced graphene oxide (rGO) using electrophoretic deposition at 300 V. The rGO modified CP results in 25% higher power density than its untreated counterpart under the same operating conditions. In comparison to the first preliminary study, the power density reported herein is more than four times higher. Additionally, the Freudenberg CPs modified with heat treatment followed by rGO deposition facing the membrane (rGOHTFM) provide the best electrolyte discharge utilization ( UE ) of 99%, followed by untreated (98%) and heat treated samples (97%) at 50 mA cm −2 . The rGOHTFM also record high charge and discharge energy efficiencies ( η E ) of 93% at the same current density, which is slightly higher than untreated CPs ( η E = 91%). Cycling the system 10 times also results in higher η E and UE for rGOHTFM CP ( η E = 92% and UE = 99% on average) in comparison to untreated electrodes ( η E = 86% and UE = 97% on average). In comparison the widely investigated SGL 10AA CP has lower efficiencies and utilization as expected ( η E = 74% and UE = 83% on average). Graphical abstract: Image 1 Highlights: Freudenberg carbon paper electrodes are studied in hydrogen/vanadium fuel cell. Freudenberg electrodes give much better charge/discharge response to SGL 10AA. Untreated samples have similar performance to rGO modified ones at 50 mA cm −2 . Reduced graphene oxide modification of heat treated samples gave best results. High cycling efficiencies (92%) and electrolyte utilization (99%) are reported.